Planning and Dynamic Control of Projects under Uncertainty - Burt, John M. (Management Science, 1977)
This paper addresses the problem of planning and controlling (through resource allocation decisions) projects under conditions of uncertainty. Particular attention is given to the dynamic reallocation of resources over the duration of projects as information about actual activity times becomes known. The effect of resource allocations on an activity is represented, by modifications in the probability function of the time to process that activity. Analytic procedures such as dynamic programming and distribution analysis, which might lead to optimal dynamic decision rules, are shown to be computationally intractable even for very small problems. For a set of project networks of relatively simple structure, the efficacy of several heuristic decision rules is tested via simulation. The results of these simulation studies indicate some general concepts that should be applicable to the management of larger, more realistic, projects.